Estudos espectroscópicos de ferritas de níquel preparadas com água de coco in natura (cocus nucifera) - Teixeira, João Damasceno (2007)
The present work is dedicated to the studies of preparation and characterization of nickel ferrites. These ferrites were synthesized by the sun-gel process in suspension of coconut natural water (cocus nucifera) ltered, prepared for Dr. Marcelo A. Macedo team, from the Department of Physics of UFSE. This new synthesis route allowed to ob- tain nanoparticles of nickel ferrites, that are prepared with the technique of formation of mixed micelles, obtained by the coconut natural water. The molecules of that suspension are called tensoatives, they are molecules associates spontaneously in aqueous solution starting from a certain concentration denominated concentration critical micellar (CMC). Above this concentration, the tensoative molecules form great molecular of colloidal di- mensions. About analytic point of view, one of the most important properties of those organized structures is their capacity of solubilize solutes of di erent characteristics. The samples were roasted for 4 hours the since 400 C up to 1200 C in a fast cooling to the ambient temperature and 1200 C to the temperature of the liquid nitrogen. The di rac- tion of ray-X (XRD), the spectroscopic Raman, Infra-red and Electronic Microscopy of Sweeping (SEM), were applied to study the dependence of the sizes of the nanoparticles of nickel ferrite, with the temperature of the thermal treatments and their correlation with their magnetic properties. The sizes of the crystallites increased of 5 nm (in the tempera- ture of the thermal treatment of 400 C) until approximately 67 nm (in the temperature of the thermal treatment of 1200 C caught a cold to the temperature of the liquid nitrogen). The crystallinity of the nanoparticles increases with the increase of the temperature of the thermal treatment. The results of the microscopy M ossbauer show that the ferrites roasted to 1200 C and caught a cold to the temperature of the liquid nitrogen to present the phase mixed spinel